IMPLEMENTASI ETIKA BISNIS ISLAM UNTUK MEMPERKUAT KINERJA DAN KEBERLANJUTAN UMKM BANJANEGARA - Cinanthya Yuwono; Dwi Kuswianto; Ovi Ariyanti (J-EBI Jurnal Ekonomi dan Bisnis Islam, 2025)
Education and the implementation of Islamic business ethics play a crucial role in strengthening the performance and sustainability of SMEs, particularly in Banjarnegara Regency. This study aims to explore the application of Islamic business ethical values as a strategy to enhance SME performance and sustainability. The research is a field study using a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving 50 SME actors in the food, beverage, and small trade sectors. The findings indicate that integrating values such as honesty, justice, trustworthiness, transparency, and social responsibility can enhance business integrity and reputation, build consumer trust, promote healthy business growth, and strengthen competitiveness through professionalism and sustainable ethical practices. Government support through market programs, training, machinery assistance, and halal certification also plays a significant role in improving product quality and expanding SME markets. In conclusion, the synergy between the application of Islamic business ethics and government support creates a tangible, measurable, and effective model of business sustainability.